Occupational Health Hazards among Women Fish Vendors in Thiruvananthapuram, Kerala - B. Kavya Vijayan ,; Vijayakumari, Sithara Balan (Indian Journal of Extension Education, 2025)
ABSTRACTThe informal sector constitutes a significant source of employment for women in India, particularly in coastal regions such as Kerala, where fish vending serves as a primary livelihood. Women fish vendors frequently encounter substantial occupational health risks stemming from extended working hours, inadequate ergonomic conditions. This study aims to examine the multifaceted occupational health hazards affecting women fish vendors in Thiruvananthapuram district, was carried out during 2025, with a particular emphasis on physical, reproductive, and psychosocial health dimensions. Employing descriptive research design, data were collected from a sample of 150 women fish vendors through structured interviews, observational checklists, and a quality of life rating scale. Statistical analyses using SPSS Version 27—including Chi-square, Fisher’s Exact Test, Mann–Whitney U, and Kruskal–Wallis H tests—were performed to explore associations between socio-demographic variables and health outcomes. Findings revealed a high incidence of musculoskeletal disorders, fatigue, dermatological conditions, and reproductive health concerns. Significant correlations were observed between health status and factors such as education level, household dependency ratio, income, and housing type. Study underscores the critical need for targeted policy interventions, comprehensive health education, infrastructural enhancements, and gender-sensitive occupational safety protocols to safeguard the health and dignity of women engaged in the unorganized sector.